Demanda energética na colheita de híbridos de milho para silagem em função do estádio de maturidade e tamanho de partícula - Factori, Marco Aurélio [UNESP]; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Silva, Paulo Roberto Arbex [UNESP]; Seki, André Satoshi [UNESP]; da Silva, Marina Gabriela Berchiol [UNESP] (My University, 2014)
Corn is the crop most used for making silage. The efficiency of the process should also be evaluated by cost per kg of dry matter harvested (kgDM). The objective of this study was to evaluate energy consumption in the harvest of corn hybrids for silage depending on the texture of the hybrid, four and three harvest maturities of particle sizes - Tp was used a tractor Massey Ferguson MF 610 model 86 cv. Cutting and harvesting the forage harvester is used model JF92 Z10. To obtain data on fuel consumption (CC) and time spent for each plot, we used a flow meter, installed near the fuel filter of the tractor. The experimental design was completely randomized in a split plot. The interaction between factors triple stage hybrid * Harvest * Tp. The velocity and displacement of the tractor were different for the maturities for hybrid hard texture. The CC schedule for hybrid dent increased harvest maturity earlier and at lower Tp. Consumption was lower by kgDM later maturity, hard texture and bite respectively. The theoretical power was higher in earlier maturity and yield were higher for hybrid hard texture in the most advanced. The CC was lower in late maturity and the hybrid hard texture can be used for silage in relation to the Cc and income in later maturity in higher Tp.
Energy demand in the harvest of corn hybrids for silage as a function of maturity stages and particle size
Keywords: Dent texture; Efficiency; Hard texture; Harvester; Silage